Manuel A. Roxas country above self - Roxas, Mar.; Tiongson, Anghelito D.; Manuel A. Roxas Foundation (Quezon City President Manuel A. Roxas Foundation, 2004)
A video documentary on President Manuel A. Roxas.
Library has: VDR-967 (1 VHS)
Produced by President Manuel A. Roxas Foundation; written and directed by Angelito Tiongson.
Executive producer: Judy A. Roxas; assistant director: Dexter Andrada.
Introduction by Senator Mar Roxas.
VHS
Keywords: Roxas, Manuel Acuna -- 1892-1948.